P590 An interim analysis of real-world safety data from an ongoing, non-interventional, observational study of patients with inflammatory bowel disease treated with CT-P13, an infliximab biosimilar, in the context of usual care with reference infliximab. (25th January 2019) - Bokemeyer, B; Hlavaty, T; Allez, M; Selema, P; Moosavi, S; Cadatal, M J; Fowler, H; Cheung, R; Lukas, M; Gisbert, J P
Abstract: Background: CT-P13 (Inflectra ® /Remsima ® ) is an infliximab biosimilar of the reference product Remicade ® (IFX-RP). We report an interim analysis of preliminary safety data for CONNECT-IBD, an ongoing, non-interventional, observational cohort study evaluating CT-P13 in the context of usual care with IFX-RP in the treatment of patients with Crohn's disease (CD) or ulcerative colitis (UC) in a real-world setting. Methods: Patients were recruited during usual care at 150 academic and community sites in 13 European countries. Adult CD or UC patients prescribed CT-P13 or EU-sourced IFX-RP at the investigator's discretion and according to the approved label were eligible. This interim analysis reports primary outcomes (drug utilisation patterns and long-term safety) for patients who received CT-P13 either as their first biologic or as continuing treatment (CT-P13) or who switched from IFX-RP to CT-P13 (Switched) based on data collection from April 2015 to December 2017. Data were analysed descriptively. Results: This analysis included 1957 patients (CT-P13, n = 1825; Switched, n = 132; Table 1). Of these, 1264 had CD, 692 had UC and 1 had missing diagnosis. Demographics and baseline characteristics were similar between groups. In total, 626 treatment-emergent adverse events (TEAEs) were reported in 438 (22.4%) patients: CT-P13 (22.2%) and Switched (25.0%). Incidences of TEAEs, serious TEAEs (12.1% vs. 12.1%) and TEAEs leading to discontinuation of study drug (8.1% vs. 6.8%) were balanced between CT-P13 and Switched groups, respectively. A higher percentage of Switched (2.3%) vs. CT-P13 (0.9%) patients discontinued from study due to AEs; however, this was likely driven by the smaller number of patients in the Switched group. Majority of patients reported TEAEs of mild-to-moderate intensity (overall: mild, 7.3%; moderate, 9.2%; severe, 5.8%). TEAEs and TEAES of special interest are summarised (Table 2). Two deaths were reported, both unrelated to study drug. Among the limitations were the difference in CT-P13 ( n = 1825) vs. Switched ( n = 132) group size and AE reporting which, due to the observational study design, had limited clinical details. Conclusions: Results from this interim analysis of CT-P13 in a real-world setting were consistent with the known safety profile of infliximab and did not identify new safety information to change the benefit–risk profile of CT-P13.